American crocodiles (Crocodylus acutus: Reptilia: Crocodilidae) visiting the facilities of a freshwater aquaculture of the Northern Pacific region, Costa Rica, carry tetracycline-resistant Escherichia coli - Mateus-Vargas, Rafael Hernán; Arias-Pérez, Verónica; Sandoval-Hernández, Iván; Hammerl, Jens Andre; Barquero-Calvo, Elías (Frontiers in Veterinary Science, 2024)
Apex predators are exposed to antimicrobial compounds and resistant microbes, which accumulate at different trophic levels of the related ecosystems. The study aimed to characterize the presence and the antimicrobial resistance patterns of fecal Escherichia coli isolated from cloacal swab samples obtained from wild-living American crocodiles (Crocodylus acutus) (n = 53). Sampling was conducted within the distinctive context of a freshwater-intensive aquaculture farm in Costa Rica, where incoming crocodiles are temporarily held in captivity before release. Phenotypic antimicrobial susceptibility profiles were determined in all isolates, while resistant isolates were subjected to whole-genome sequencing and bioinformatics analyses. In total, 24 samples contained tetracycline-resistant E. coli (45.3%). Isolates carried either tet(A), tet(B), or tet(C) genes. Furthermore, genes conferring resistance to ß-lactams, aminoglycosides, fosfomycin, sulfonamides, phenicol, quinolones, trimethoprim, and colistin were detected in single isolates, with seven of them carrying these genes on plasmids. Genome sequencing further revealed that sequence types, prevalence of antibiotic resistance carriage, and antibiotic resistance profiles differed between the individuals liberated within the next 24 h after their capture in the ponds and those liberated from enclosures after longer abodes. The overall presence of tetracycline-resistant E. coli, coupled with potential interactions with various anthropogenic factors before arriving at the facilities, hinders clear conclusions on the sources of antimicrobial resistance for the studied individuals. These aspects hold significant implications for both the aquaculture farm’s biosecurity and the planning of environmental monitoring programs using such specimens. Considering human-crocodile conflicts from the One Health perspective, the occurrence of antimicrobial resistance underscores the importance of systematical surveillance of antibiotic resistance development in American crocodiles.